Geomorphometric analysis of the 2014-2015 Bárðarbunga volcanic eruption, Iceland - Dirscherl, Mariel Christina; Rossi, Cristian (Remote Sensing of Environment, 2018)
Topographical information is of fundamental interest for a wide range of disciplines including glaciology, agriculture, communication network planning, or hazard management. In volcanology, elevation data are of particular importance when assessing material flows throughout a volcanic system. To obtain accurate estimates of time-varying topography in volcanic active regions, high-resolution digital elevation models (DEMs) are required. To monitor and evaluate topographical changes and especially volumetric gains and losses during the 2014-2015 Bárðarbunga eruption, Iceland, multi-temporal TanDEM-X DEM sequences were evaluated. The 2014-2015 volcanic eruption was associated with the rare event of a caldera collapse, visible on the surface of the Vatnajökull glacier, as well as major lava effusion in the Holuhraun plain. Before investigating topographical change at the two study areas, the TanDEM-X DEMs were analysed for absolute and relative height errors resulting from the radar system parameters, the SAR processing or the local environment. The uncertainty investigation determined that acquisitions over the snow-covered Bárðarbunga caldera were primarily affected by microwave penetration into snow and DEMs over the Holuhraun lava field exhibited increased height errors due to active lava flows and dynamic outwash plain. The topographical analysis of the 2014-2015 Bárðarbunga eruption revealed a maximum vertical displacement of approximately -65 m and +43 m at the study area of the Bárðarbunga caldera and Holuhraun lava field respectively. With a total subsidence volume of -1.40 ± 0.13 km3 and a dense-rock equivalent (DRE) lava volume of +1.36 ± 0.07 km3, known uncertainties in volume were decreased by approximately 35% and 77% accordingly. Taking into account the calculation of rates, the temporal development of caldera collapse and lava effusion was found to exhibit a near-exponential decrease. The ratio between subsidence and DRE lava volume moreover indicated the coupling between piston collapse and magma ...